Computing voter transitions: The elections for the Catalan Parliament, from 2010 to 2012 - Albert Corominas; Amaia Lusa; M. Dolors Calvet (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: To estimate the transition rates corresponding to the 2010 and 2012 elections to the Catalan Parliament for the four constituencies in which Catalonia is divided for this purpose. The main features of the results, which are obtained by means of mathematical programming, are commented. Design/methodology/approach: Mathematical programming optimization models are formulated in order to find the transition rates that yield a better adjust between the actual results in 2012 and those computed applying the transition rates to the 2010 results. The transition rate matrices are estimated for each one of the four constituencies, since the set of options is not the same for all them. No other assumptions that those of numerical consistency are adopted. Findings: The transition rate models provide satisfactory goodness of fit. Mathematical programming turns out to be an easy-to-use tool for estimating the transition rates and, at the same time, very flexible, since, if necessary, it allows incorporating the constraints corresponding to additional assumptions. Originality/value: The transition rates from 2010 to 2012 in Catalonia are particularly interesting, since 2012 results implied a significant change in the composition of the Catalan Parliament. To the best of our knowledge, no other scientific journal paper has dealt with this question. Our results are available to the researchers in order to interpret the change and try to foresee future flows of voters.
Keywords: 650; voter transitions; electoral change; mathematical programming